(untitled) (Annals of Medical Research, 2022)
Aim: Allergic contact dermatitis (ACD) is a delayed hypersensitivity reaction to specific allergens that come in contact with the skin. Detection of the culprit allergen plays a central role in the effective treatment and management of this chronic disease. The present study aims to report distribution of allergens that cause ACD by analyzing patch test results, and investigate atopic background of these patients. Materials and Methods: Results from patch tests performed on patients with ACD in the Department of Adult Allergy and Clinical Immunology at a tertiary hospital in Anatolian side of Istanbul were retrospectively assessed. Data regarding age, gender, occupation, lesion localization, history of suspected exposure, total Immunoglobulin E levels, concomitant allergic rhinitis and skin prick test results were inspected. Results: Of the 131 patients, female/male ratio was 91 (69.5%)/40 (30.5%). Patch test results were negative in 56 (42.7%) patients, and positive for at least one allergen in 75 (57.3%) patients. Five most common allergens with a positive result were nickel sulphate (25.2%), gold sodium thiosulfate (13%), cobalt (9.9%), thiomersal (9.9%), and colophony (5.3%), respectively. A comparison between patch test results and genderdid not demonstrate any statistical significance. Young patients had a significantly higher positive reaction to thiomersal (p=0,008). No correlation was found between atopic background and ACD. Conclusion: Patch test results significantly contribute in the differential diagnosis and management of patients with dermatitis. Metals and thiomersal were the most common allergens detected by patch tests in our study. This is in correlation with previous research. We believe that types of allergens may go through an alteration as the environment and lifestyle changes over time, and that our findings contribute to determine which allergens to be used in patch tests in the future.